INOVASI SISTEM INFORMASI PENDATAAN RUMAH TIDAK LAYAK HUNI (SIGAP-RTLH) OLEH DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN GRESIK - Liza Alvini Sahrin; Trenda Aktiva Oktariyanda (Publika, 2022)
The Gresik Regency Housing and Settlement Office created an information system innovation to address settlement problems in the implementation of the Uninhabitable House Handling Program, the innovation is web-based and in the form of the SIGAP-RTLH smartphone application (Information System for Uninhabitable House Data). This innovation was created as a means of accelerating poverty alleviation for people who occupy uninhabitable houses by supporting data collection and updating integrated Uninhabitable House data against the background of the urgency of data collection and the preparation of proposals for uninhabitable houses that take a long time. The purpose of this study was to describe the innovation of the Uninhabitable House Data Collection Information System (SIGAP-RTLH) by the Gresik Regency Housing and Settlement Area. The method used is a descriptive research method with a qualitative approach according to Miles and Huberman (Sugiyono, 2015). The purpose of this study is to describe how the Innovation of the Uninhabitable House Data Collection Information System (SIGAP-RTLH) by the Gresik Regency Housing and Settlement Area is based on the innovation criteria according to the Regulation of the Minister of State Apparatus Empowerment of the Republic of Indonesia Number 5 of 2019 concerning Public Service Innovation Competitions within the Ministry/ Local Government Institutions, State/Regional Owned Enterprises, which are novel, effective, useful, transferable/replicated, and sustainable. Data collection techniques through interviews, observation, and also documentation. The data analysis technique used in writing this report is the technique according to Miles and Huberman (Sugiyono, 2015) namely data collection, data reduction, data presentation, and drawing conclusions.